The Community Satisfaction Analysis in Mangrove Forests Management in the Unit X KPHL Batu Bara Using Importance Performance Analysis - Ginting, Eva Maria Natalina; Zaitunah, Anita; Syahputra, OK Hasnanda (Universitas Gadjah Mada, 2025)
Sustainable forest management encompasses a holistic approach that considers forests' ecological, social, and economic functions. However, an increasing focus on economic functions often leads to the neglect of social and ecological aspects. Consequently, it is essential to evaluate community satisfaction regarding the service performance of forest management units (FMUs). This research aimed to assess community satisfaction with the service performance of Unit X KPHL Batu Bara, which oversees coastal forests primarily comprised of mangrove ecosystems in the coastal regions of Batu Bara Regency, North Sumatra, utilizing Importance Performance Analysis (IPA). The findings revealed that the service performance of Unit X KPHL Batu Bara falls short of community expectations, as indicated by a negative average gap score of -0.716 between service performance and expectations. The categories of assurance and tangibles exhibited the highest gap scores. Therefore, Unit X KPHL Batu Bara must enhance their service quality for the local communities.